Menghidupkan Nilai Kejujuran dan Kebahagiaan Melalui Buku Saku - Putri, Kurnia Maisya; Minarsih, Dini; Putri, Salsabila Meilani; Nashir, Raka Abdul; Timur, Pradipa Fazli; Hayati, Aulia Aenul (Universitas Pahlawan Tuanku Tambusai, 2025)
This study developed and tested the effectiveness of a pocket book based on Living Values Education (LVE) in promoting honesty and happiness among sixth-grade students. A (mixed methods) approach with an _explanatory sequential_ design was used. Quantitative data were from 22 student questionnaires, and qualitative data from teacher and parent interviews. The book integrated local values and socio-emotional aspects. Results showed increased understanding of values (average score 87–90%), supported by positive behavioral changes. The pocket book proved effective as a moral education tool.